2001
DOI: 10.1515/cclm.2001.023
|View full text |Cite
|
Sign up to set email alerts
|

Metal Exposure from Amalgam Alters the Distribution of Trace Elements in Blood Cells and Plasma

Abstract: Twenty-seven consecutive patients with health problems associated with dental amalgam were recruited. In spite of thorough medical examinations, there were no diagnoses available. The patient group was dominated by women. A healthy age- and sex-matched control group with dental amalgams without symptoms was also recruited. Metal level monitoring in plasma and nuclear microscopy of isolated individual blood cells were carried out. Significant increases of copper, iron, zinc and strontium were found in patient p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 54 publications
(33 reference statements)
1
5
0
1
Order By: Relevance
“…Earlier studies in our laboratory further corroborated this observation [11,12]. Our findings showed statistical significance in a comparison of Hg levels in blood plasma between control individuals and patients with ill health attributed to dental amalgams.…”
Section: Introductionsupporting
confidence: 90%
“…Earlier studies in our laboratory further corroborated this observation [11,12]. Our findings showed statistical significance in a comparison of Hg levels in blood plasma between control individuals and patients with ill health attributed to dental amalgams.…”
Section: Introductionsupporting
confidence: 90%
“…It has been reported that the human metabolism is affected by certain toxic metals even at trace levels, thus influencing many body functions significantly [3,4]. Some of the metals have also been found to affect cellular transfer and the levels of other important minerals and nutrients that have significant health effects [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Human metabolism may be affected by certain metals even at trace levels and thus associated with numerous health effects (Robinson et al 1973;Goyer 1993;Hayes 1997;Lindh et al 2001). A number of biological processes have been linked with the imbalances of trace metals (Boadi et al 1992;Singh and Garg 1998;Semczuk and Semczuk-Sikora 2001).…”
mentioning
confidence: 99%